Peer to peer ranging system: software development - Lim, Yu Feng (Nanyang Technological University, 2022)
This report provides an overview of how a peer to peer ranging system is implemented using ultra-wideband (UWB) technology and its accuracy and performance is assess. The paper begins with a brief explanation on the background on UWB and its advantages for it to be use for ranging purposes. The paper then proceed to provide further details on UWB and its standard and how it can be implemented using Decawave MDEK 1001 development as the hardware together with SEGGER embedded studio for ARM processor as the software for the development of the firmware to control the UWB transceiver. Range derived using UWB are compared against the ground truth to assess its accuracy and sources of error are discussed. The paper concludes with a summary and recommendations for future work.